2016
DOI: 10.18203/2320-6012.ijrms20162956
|View full text |Cite
|
Sign up to set email alerts
|

Aseptic-clinical hand hygiene knowledge survey amongst health care workers in a tertiary care hospital in Western India

Abstract: Background: Maintenance of hand hygiene among health care workers (HCWs) is the cornerstone of infection prevention and control programmes in a health care facility. Poor hand hygiene amongst HCWs is the single most common cause of cross-transmission of infections between patients and HCWs in the hospital. The objective of this study was to identify the risk factors for non-adherence and assess the knowledge regarding maintenance of hand hygiene amongst health care workers at a tertiary health care centre in W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Prior training in hand hygiene was found to be significantly associated with the participants’ knowledge of hand hygiene which was similar to the findings of Vaishnav B et al . [ 1 ] showing that training has a positive relationship with knowledge.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior training in hand hygiene was found to be significantly associated with the participants’ knowledge of hand hygiene which was similar to the findings of Vaishnav B et al . [ 1 ] showing that training has a positive relationship with knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…Maintenance of proper hand hygiene among treating doctors and nurses is one of the most important measures to curb health-care-associated infections. [ 1 ] Hand hygiene is one of the most important healthcare concerns globally and is a single most cost-effective and practical measure to cut down infections and spread of antimicrobial resistance across all settings—from advanced health-care systems to primary health-care centers. [ 2 3 4 ] WHO introduced the “My five moments with hand hygiene” approach for health-care workers and these are before and after touching a patient, before performing aseptic procedures, after exposure to body fluids, and after touching patient surroundings.…”
Section: Introductionmentioning
confidence: 99%
“…[10] Knowledge about hand hygiene products should be explained to the staff in their own language and give them the choice to follow one product only. A study in Pune showed that Knowledge about the differences between ABHR and hand washing with soap and water was poor overall amongst the study population [9] Among the rural parts of India, the most common product used are soap and water (63-82%), followed by spirit or Alcohol based hand rubs which was highest in the OTs (54%). Other optional materials included 'Only water', 'Water and antiseptic solution' and 'Water and liquid soap.…”
Section: Various Hand Hygiene Products Usedmentioning
confidence: 94%
“…A total of 91.48% participants answered "always" in response for actually performing hand hygiene (practice) after a body fluid exposure risk (Moment 3), but for the rest of the moments (Moment 1, 2, 4, 5) the response was poor (<70%). [9] Five Moments of Hand Hygiene When we compare the practice of the five moments of hand hygiene with the nursing staff it is seen that 65% of the nursing staff do not practice hand washing before patient contact compared to 15% of nurses who always practice hand hygiene. 40% never washed hands before an aseptic procedure and 20% never washed hands after patient contact.…”
Section: Attitude Of Nurses and Technicians Towards Hand Hygienementioning
confidence: 99%
“…6 Awareness on hand hygiene practices among health care workers is less as shown in many studies. 7 Medical and nursing students are exposed to hospital acquired infections during their training and it is necessary that they should be aware of hand hygiene. 8 The reasons for not practicing appropriate hand hygiene practices are lack of knowledge about guidelines, lack of facilities, insufficient time, patient overload, lack of priority by the institutions.…”
Section: Introductionmentioning
confidence: 99%